Promoting Listening Fluency in Pre-Intermediate EFL Learners Through Meaningful Oral Tasks (2018)
This article reports a study on the implementation of meaningful oral tasks to promote listening fluency in ten pre-intermediate English as a foreign language learners in the English language teaching program at a Colombian public university. The tasks were implemented to overcome the weaknesses these students had to understand oral messages from audio materials and daily-life conversations in classes. A qualitative action-research study with observation field-notes and semi-structured interviews served as the basis for this research. Results indicate that this methodology provided suitable opportunities to foster listening fluency through the development of meaningful oral tasks. Participants developed dynamic assignments that included pre, while, and post intensive-extensive listening practices which allowed them to understand, to interpret oral messages, and to provide suitable responses to do the required tasks.